CLASSICAL MOLECULAR DYNAMICS (MD) SIMULATION OF SALT AND SOLVENT SOLVATION EVENTS IN LITHIUM ION BATTERIES TO DETERMINE ENERGY FLUCTUATIONS - Ngaderman, Hubertus; Sinaga, Ego Srivajawaty; Bungasalu, Benny Abraham (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2025)
This study looks at how salt and solvent mix, as shown by the final positions of particles in a simulation. The simulation uses Lennard-Jones parameters and runs in a closed system with fixed energy. The goal is to see if the particles follow the Maxwell velocity distribution. When lithium hexafluorophosphate salt mixes with ethylene carbonate, solvation occurs. The simulation runs for 100 and 2000 steps to get accurate results. At the start, no chemical reactions or outside forces are involved just the natural movement of particles. For fluorine, after 2000 steps, the particles start to group in one area, showing the system isn’t balanced yet. Since velocity is linked to kinetic energy, it's important to look at the most common speeds of lithium, phosphorus (P), fluorine (F), and lithium-oxygen carbonyl (Li-OC). At 100 steps, the speed data looks good for lithium, phosphorus, and fluorine, except for how fluorine interacts with itself. So, the number of steps was increased to 2000. But even then, the particles don’t spread out fully, which isn’t realistic nature doesn’t leave space. That’s why the simulation should run up to 3000 steps for better, more realistic results.